The modernisation of Russia, 1676-1825 - Dixon, Simon (Simon M.) (New approaches to European history., 1999)
"This is the first book to place Russia's 'long' eighteenth century squarely in its European context. The conceptual framework is set out in an opening critique of modernisation theory which, while rejecting its linear implications, maintains its focus on the relationship between government, economy, and society. Following a chronological introduction, a series of thematic chapters emphasise the ways in which Russia's international ambitions as an emerging great power provoked administrative and fiscal reforms with wide-ranging (and often unanticipated) social consequences."--Jacket